FACTORS CAUSING STRESS IN TYPE 2 DIABETES MELLITUS PATIENTS - Ayu Nursucita; Lina Handayani (Universitas Negeri Gorontalo, 2021)
Diabetes mellitus is a dangerous disease caused by increased glucose levels, increased diabetes mellitus is caused by genetic factors, obesity, sudden lifestyle changes, wrong diet, non-compliance in taking medication, lack of exercise, age, smoking and stress. The purpose of this literature study is to discuss the factors that cause stress in people with diabetes mellitus type 2. The method used is a literature review study, the literature used is a National Journal published from 2011 to 2021. Literature was collected through the database https://garuda.ristekbrin.go.id/ and google scholar by using the search words